Manipulations of Glutathione Metabolism Modulate IP3-Mediated Store-Operated Ca2+ Entry on Astroglioma Cell Line - Mokrane, Nawfel; Snabi, Yassin; Cens, Thierry; Guiramand, Janique; Charnet, Pierre; Bertaud, Anaïs; Menard, Claudine; Rousset, Matthieu; de Jesus Ferreira, Marie-Céleste; Thibaud, Jean-Baptiste; Cohen-Solal, Catherine; Vignes, Michel; et al. (Frontiers in Aging Neuroscience, 2021)
The regulation of the redox status involves the activation of intracellular pathways as Nrf2 which provides hormetic adaptations against oxidative stress in response to environmental stimuli. In the brain, Nrf2 activation upregulates the formation of glutathione (GSH) which is the primary antioxidant system mainly produced by astrocytes. Astrocytes have also been shown to be themselves the target of oxidative stress. However, how changes in the redox status itself could impact the intracellular Ca2+ homeostasis in astrocytes is not known, although this could be of great help to understand the neuronal damage caused by oxidative stress. Indeed, intracellular Ca2+ changes in astrocytes are crucial for their regulatory actions on neuronal networks. We have manipulated GSH concentration in astroglioma cells with selective inhibitors and activators of the enzymes involved in the GSH cycle and analyzed how this could modify Ca2+ homeostasis. IP3-mediated store-operated calcium entry (SOCE), obtained after store depletion elicited by Gq-linked purinergic P2Y receptors activation, are either sensitized or desensitized, following GSH depletion or increase, respectively. The desensitization may involve decreased expression of the proteins STIM2, Orai1, and Orai3 which support SOCE mechanism. The sensitization process revealed by exposing cells to oxidative stress likely involves the increase in the activity of Calcium Release-Activated Channels (CRAC) and/or in their membrane expression. In addition, we observe that GSH depletion drastically impacts P2Y receptor-mediated changes in membrane currents, as evidenced by large increases in Ca2+-dependent K+ currents. We conclude that changes in the redox status of astrocytes could dramatically modify Ca2+ responses to Gq-linked GPCR activation in both directions, by impacting store-dependent Ca2+-channels, and thus modify cellular excitability under purinergic stimulation.